Keanekaragaman Makrofauna Tanah pada Habitat Hutan Homogen dan Heterogen di Kawasan Hutan Pendidikan dan Pelatihan Sisimeni Sanam, Kabupaten Kupang, Nusa Tenggara Timur - Maria M. E. Purnama; Nixon Rammang; Astin Elise Mau; Roni Haposan Sipayung (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2022)
This study aims to determine types of soil macrofauna and analyze the diversity and similarity of soil macrofauna contained in homogeneous and heterogeneous forest habitat. This research has been done in the Sisimeni Sanam Education and Training Forest Area, in Silu Village, Fatuleu District, Kupang Regency, East Nusa Tenggara. This research is descriptive quantitative using the exploratory method. Observations were carried out through pitfall trap and hand sorting. The data to be analyzed is related to the diversity index (H') and the Similarity Index (IS). Analysis of data using Microsoft Excel and Past3 applications. The results showed that types of soil macrofauna in Forest Areas Education and Training Sisimeni Sanam especially under the stands of forest habitat heterogeneous and homogeneous forest consists of 11 ordo with a total of 1,113 individuals were found. The diversity level of soil macrofauna under heterogeneous and homogeneous forest habitat stands at 1.71063 and 0.55568. The level of similarity between soil macrofauna under heterogeneous forest habitat stands is high with an average value of 62.406%.